Analisis Strategi Komunikasi PT Kereta Api Indonesia (KAI) DIVRE II Sumatera Barat Dalam Penanganan Kecelakaan Kereta Api di Kota Padang - Tahlia Amanda; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study is motivated by the high frequency of railway accidents in Padang City, which not only affect safety aspects but also generate public communication issues that influence public trust in institutions. The research aims to analyze the communication strategies implemented by PT Kereta Api Indonesia (KAI) Regional Division II West Sumatra in handling railway accident issues. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that PT KAI perceives accidents as reputational crises that require responsive and adaptive communication strategies. The strategies include centralized information dissemination through a single-gate system, the use of official spokespersons to maintain message consistency, and the utilization of mass media and social media for information distribution. In addition, the company emphasizes a balance between the speed and accuracy of information while prioritizing empathy toward victims. Despite challenges such as limited initial data and the rapid flow of digital information, a structured communication strategy is effective in managing public perception. This study concludes that effective communication strategies play a crucial role in maintaining organizational reputation and public trust